2019
DOI: 10.1016/j.neuron.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying Microbial-Mediated Changes in Social Behavior in Mouse Models of Autism Spectrum Disorder

Abstract: Highlights d Treatment with L. reuteri rescues social deficits in several ASD mouse models d L. reuteri reverses social deficits via the vagus nerve d L. reuteri reverses social deficits even in germ-free mice d OXTR inhibition prevents L. reuteri's effects on social behavior and VTA plasticity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
494
3
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 588 publications
(525 citation statements)
references
References 104 publications
18
494
3
10
Order By: Relevance
“…Microbes residing in the GI tract regulate mood and behavior via the microbiota-gut-brain axis [Cryan & O'Mahony, 2011;Foster & McVey Neufeld, 2013]. Several studies have shown altered microbial signatures in ASD patient populations [Luna et al, 2017;Mayer et al, 2014] and report dysbiosis in rodent models demonstrating ASD relevant behaviors [de Theije et al, 2014;Hsiao et al, 2013;Sgritta et al, 2019]. We therefore assessed whether GI dysfunction could potentially impact the structure and function of fecal microbes in NL3 R451C mice.…”
Section: Introductionmentioning
confidence: 99%
“…Microbes residing in the GI tract regulate mood and behavior via the microbiota-gut-brain axis [Cryan & O'Mahony, 2011;Foster & McVey Neufeld, 2013]. Several studies have shown altered microbial signatures in ASD patient populations [Luna et al, 2017;Mayer et al, 2014] and report dysbiosis in rodent models demonstrating ASD relevant behaviors [de Theije et al, 2014;Hsiao et al, 2013;Sgritta et al, 2019]. We therefore assessed whether GI dysfunction could potentially impact the structure and function of fecal microbes in NL3 R451C mice.…”
Section: Introductionmentioning
confidence: 99%
“…After being given vitamin B6, autistic children439 have a reduced urinary homovanillic acid, which suggests an improved 440 dopamine metabolism(Lelord et al, 1978). These studies suggest the 441 regulated role of vitamin B6 in dopaminergic metabolites in ASD patients.442Previously, Sgritta reported the modulated VTA plasticity by Lactobacillus 443 reuteri in ASD mouse models(Sgritta et al, 2019). Here, our study showed a444 new regulatory role of gut microbiota on dopamine in PFC by modulating 445 vitamin B6 in EphB6-deficient mice.…”
mentioning
confidence: 54%
“…Germ‐free rodents typically exhibit deficits in both sociability and memory for social stimuli (indexed by preference for a novel social partner; Buffington et al, ; Desbonnet et al, ; Sgritta et al, ; Stilling et al, ; but see also Arentsen et al, ). Similar effects are observed following antibiotic depletion of the microbiota during development (Degroote et al, ; Desbonnet et al, ), while administration of certain probiotic species can enhance social behavior in various murine models of autism (Buffington et al, ; Hsiao et al, ; Sgritta et al, ) and inflammation‐induced social withdrawal (D'Mello et al, ). In fruit flies ( Drosophila melanogaster ), both developing and mature individuals rely on microbiota‐derived volatile compounds as social signals, influencing food and mating preference (Sharon et al, ; Venu et al, ).…”
Section: Evidence For Microbial Modulation Of Neurocognitive Developmentmentioning
confidence: 99%
“…Lesion of the vagus nerve prevents the behavioral effects of certain probiotics (Bravo et al, 2011;Sgritta et al, 2019). Most recently, it was shown that vagotomy at weaning prevented the rescue of social behavior by probiotic treatment in a genetic mouse model of autism (Sgritta et al, 2019).…”
Section: The Vagus Nervementioning
confidence: 99%